Respostas
respondido por:
1
3x-y=-5
x+y=3
(Cancela -y com +y e temos:)
4x=-2
x=-2/4(simplificando por 2,temos:)
x=-1/2
x + y = 3
-1/2 + y = 3
y=3+1/2
2y=6+1
2y=7
y=7/2
x+y=3
(Cancela -y com +y e temos:)
4x=-2
x=-2/4(simplificando por 2,temos:)
x=-1/2
x + y = 3
-1/2 + y = 3
y=3+1/2
2y=6+1
2y=7
y=7/2
respondido por:
0
3x - y = - 5
x + y = 3
--------------
4x = -2
x = - 2/4 (÷2)
x = - 1/2
x + y = 3
- 1/2 + y = 3
y = 3 + 1/2 (2)
2y = 6 + 1
2y = 7
y = 7/2
Resposta:
x = - 1/2
y = 7/2
x + y = 3
--------------
4x = -2
x = - 2/4 (÷2)
x = - 1/2
x + y = 3
- 1/2 + y = 3
y = 3 + 1/2 (2)
2y = 6 + 1
2y = 7
y = 7/2
Resposta:
x = - 1/2
y = 7/2
Perguntas similares
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás